Universal Theory of Light Scattering of Randomly Oriented Particles: A Fluctuational-Electrodynamics Approach for Light Transport Modeling in Disordered Nanostructures - Ramirez-Cuevas, Francisco V; Gurunatha, Kargal L; Parkin, Ivan P; Papakonstantinou, Ioannnis (ACS photonics, 2022)
Disordered nanostructures are commonly encountered in many nanophotonic systems, from colloid dispersions for sensing to heterostructured photocatalysts. Randomness, however, imposes severe challenges for nanophotonics modeling, often constrained by the irregular geometry of the scatterers involved or the stochastic nature of the problem itself. In this Article, we resolve this conundrum by presenting a universal theory of averaged light scattering of randomly oriented objects. Specifically, we derive expansion-basis-independent formulas of the orientation-and-polarization-averaged absorption cross section, scattering cross section, and asymmetry parameter, for single or a collection of objects of arbitrary shape. These three parameters can be directly integrated into traditional unpolarized radiative energy transfer modeling, enabling a practical tool to predict multiple scattering and light transport in disordered nanostructured materials. Notably, the formulas of average light scattering can be derived under the principles of fluctuational electrodynamics, allowing the analogous mathematical treatment to the methods used in thermal radiation, nonequilibrium electromagnetic forces, and other associated phenomena. The proposed modeling framework is validated against optical measurements of polymer composite films with metal-oxide microcrystals. Our work may contribute to a better understanding of light-matter interactions in disordered systems, such as plasmonics for sensing and photothermal therapy, photocatalysts for water splitting and CO dissociation, photonic glasses for artificial structural colors, and diffuse reflectors for radiative cooling, to name just a few.